DIPG-30. ISOFORM SPECIFIC OVEREXPRESSION OF WILMS' TUMOR PROTEIN IN DIFFUSE INTRINSIC PONTINE GLIOMAS. (23rd April 2019) - Lee, Sulgi; Kambhampati, Madhuri; Yadavilli, Sridevi; Gordish-Dressman, Heather; Gaonkar, Krutika; Raman, Pichai; Cruz, Conrad; Packer, Roger; Almira-Suarez, M Isabel; Becher, Oren; Resnick, Adam; Mueller, Sabine; et al.
Abstract: Diffuse intrinsic pontine glioma (DIPG) is a deadly pediatric brain cancer constituting 10–15% of all central nervous system (CNS) tumors in children. Its anatomical location and infiltrative nature make it one of the most challenging tumors to treat. As such, targeted therapies are gaining more interest in CNS tumors. To identify a suitable therapeutic target, we evaluated publicly available gene expression data of pediatric glioblastoma specimens (n=34, GSE50161), DIPG specimens (n=35, GSE50021) and gene expression data of DIPG specimens from our previous dataset (n=5). Further analysis using 37 pediatric midline glioma specimens collected at autopsy in accordance with Children's National Health System Institutional Review Board approval, indicated overexpression of one candidate protein, Wilms' tumor protein (WT1), by immunohistochemistry. Interestingly, our immunohistochemistry and immunofluorescence analysis showed that WT1 in DIPG specimens is localized in the cytoplasm. Real-Time Quantitative Reverse Transcription PCR analysis using fresh frozen tumor specimens also showed that H3.3K27M-DIPG subtypes (n=3) to express higher levels of WT1 protein compared to those with H3.1K27M (n=2) (5.3 fold). More importantly, RNA-seq analysis of DIPG tumors (n=23) revealed specific transcriptome expression of WT1 transcript variant F. Nuclear export signal prediction analysis of the WT1 protein sequence translated by this transcript showed a higher nuclear export signal prediction score compared to other isoforms of WT1. Our findings suggest that WT1, particularly WT1 variant F, is a robust tumor specific antigen in DIPG, which may reveal its biological role in tumorigenesis and may have implications for clinical translation as an immunotherapeutic target.